Amniotic band associated with human tail-like cutaneous appendage and spinal dermoid tumor: An exceedingly rare triad - Leopoldo Mandic Ferreira Furtado; José Aloysio da Costa Val Filho; Bruno Lacerda Sandes; Gustavo Alberto Rodrigues da Costa; Fernando Levi Alencar Maciel; Eustaquio Claret dos Santos Júnior (Archives of Pediatric Neurosurgery, 2020)
Introduction: The association between amniotic band syndrome (ABS) and spinal dysraphism is an extremely rare entity that was paucity reported in the literature so far and similar conditions such multiple asymmetric encephaloceles and anencephaly were also previously described with ABS.